The monopolistic competition revolution in retrospect - Brakman, Steven; Heijdra, Ben J. (Cambridge University Press, 2004)
In 1977 a seminal paper was published by Avinash Dixit and Joseph Stiglitz that revolutionized the modeling of imperfectly competitive markets. It launched what might be called the second monopolistic competition revolution which has been far more successful than the first one, initiated by Edward Chamberlin and Joan Robinson in the 1930s. In this collection of original essays experts in the fields of macroeconomics, international trade theory, economic geography, and international growth theory address the question of why the second revolution was so successful. They also highlight what is missing, and look forward to the next step in the modeling of imperfectly competitive markets. The text includes a comprehensive survey of both monopolistic competition revolutions, and previously unpublished working papers by Dixit and Stiglitz that led to their famous 1977 paper. With original contributions from Dixit, Ethier, Neary and Stiglitz amongst others, this collection will excite interest amongst researchers, advanced students and economists.